The The Concept of Al-Hisbah in Indonesia’s Modern Islamic Economy: Sharia Supervision in the Era of Blockchain and AI - Ahmada Khoirul Umam (Jesya, 2026)
This article examines how Al-Hisbah, as an economic supervisory institution, intersects with various modern digital advancements. The study employs a descriptive-normative literature review methodology. The findings indicate that Al-Hisbah remains highly relevant and has strong potential to be integrated into unified systems with modern innovations such as blockchain and artificial intelligence. Nevertheless, several important considerations must be emphasized to ensure the system operates optimally while remaining aligned with Islamic principles. In the result, this study explain a unified conceptual framework that can be derived from al-hisbah, a classical economic instrument, in relation to modern concepts, namely blockchain and artificial intelligence (AI). Furthermore, the discussion is structured into four main points, covering the urgency of each concept, the process of their integration, and the challenges that may hinder such integration